O-GlcNacylation Links TxNIP to Inflammasome Activation in Pancreatic β Cells - Filhoulaud, Gaelle; Benhamed, Fadila; Pagesy, Patrick; Bonner, Caroline; Fardini, Yann; Ilias, Anissa; Movassat, Jamileh; Burnol, Anne-Françoise; Guilmeau, Sandra; Kerr-Conte, Julie; Pattou, François; Issad, Tarik; et al. (Frontiers in Endocrinology, 2019)
Thioredoxin interacting protein (TxNIP), which strongly responds to glucose, has emerged as a central mediator of glucotoxicity in pancreatic β cells. TxNIP is a scaffold protein interacting with target proteins to inhibit or stimulate their activity. Recent studies reported that high glucose stimulates the interaction of TxNIP with the inflammasome protein NLRP3 (NLR family, pyrin domain containing 3) to increase interleukin-1 β (IL1β) secretion by pancreatic β cells. To better understand the regulation of TxNIP by glucose in pancreatic β cells, we investigated the implication of O-linked β-N-acetylglucosamine (O-GlcNAcylation) in regulating TxNIP at the posttranslational level. O-GlcNAcylation of proteins is controlled by two enzymes: the O-GlcNAc transferase (OGT), which transfers a monosaccharide to serine/threonine residues on target proteins, and the O-GlcNAcase (OGA), which removes it. Our study shows that TxNIP is subjected to O-GlcNAcylation in response to high glucose concentrations in β cell lines. Modification of the O-GlcNAcylation pathway through manipulation of OGT or OGA expression or activity significantly modulates TxNIP O-GlcNAcylation in INS1 832/13 cells. Interestingly, expression and O-GlcNAcylation of TxNIP appeared to be increased in islets of diabetic rodents. At the mechanistic level, the induction of the O-GlcNAcylation pathway in human and rat islets promotes inflammasome activation as evidenced by enhanced cleaved IL1β. Overexpression of OGT in HEK293 or INS1 832/13 cells stimulates TxNIP and NLRP3 interaction, while reducing TxNIP O-GlcNAcylation through OGA overexpression destabilizes this interaction. Altogether, our study reveals that O-GlcNAcylation represents an important regulatory mechanism for TxNIP activity in β cells.